Implementation of the independent learning curriculum student achievement at SMP Negeri 1 Bengkalis - Afrizal, Ali; Supardi, Supardi (Junal Ilmu Manajemen, 2024)
This research aims to examine, analyze and interpret the description of the implementation of the independent learning curriculum on student achievement at SMP Negeri 1 Bengkalis. The aspect of the readiness of teaching staff in implementing the independent learning curriculum based on competency, innovation, creativity and work ethic is a driving factor in increasing student achievement at SMP Negeri 1 Bengkalis. These four aspects support effective learning strategies and models. This research is descriptive in nature using a qualitative approach. Data was obtained from interviews with a number of informants, namely teachers at SMP Negeri 1 Bengkalis who implemented the independent learning curriculum. The results of the research show that there is an optimal implementation of the Independent Learning curriculum which is able to increase student achievement, and it is also found that there are obstacles, namely the culture of learning. The key to successful implementation of the independent learning curriculum is that teachers and students increase the mindset of wanting to make new breakthroughs so that the results achieved can be maximized. Since implementing the independent learning curriculum in the last two years at SMP Negeri 1 Bengkalis, teachers have changed their mindset in order to achieve educational goals effectively, creating strategies and supporting this by applying competency to teachers. It can be seen that student achievement has increased, the independent learning curriculum contributes to increasing student achievement because in the independent learning curriculum the modules created are determined according to students' interests and learning styles so that all students can achieve. The Strengthening Pancasila Student Profile Project is an independent curriculum program that did not exist in the previous curriculum to strengthen various competencies in the Pancasila student profile. This is interrelated and is a supporting factor in increasing student achievement in the implementation of the independent learning curriculum at SMP Negeri 1 Bengkalis.